Law No. 24 of the year 2020 Concerning Certain Financial Rules Needed to Deal with the Repercussions Resulting From The Novel Coronavirus (Covid-19) = قانون رقم 24 لسنة 2020 ببعض القواعد المالية التى يتطلبها التعامل مع التداعيات التى يخلفها فيروس كورونا المستجد (كوفيد-19) - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic